A Description 0f the Level of Satisfaction of Family Planning (KB) Acceptors with Long-Term Contraceptive Method Services (MKJP)) - Assofi, A. Amanda Maharani; Saimin, Juminten; Yulia, Andi (Faculty of Medicine, Universitas Mataram, 2025)
Abstract. The increasingly discussed contraceptive method is the long-term contraceptive method, which offers safety, effectiveness, and comfort. However, the implementation of family planning services is still not optimal, as can be seen from the low participation in the MKJP. The prevalence of MKJP usage according to SDKI baseline data in 2019 is 21.39% while the 2024 RPJMN target is 28.39%. The thing that affects participation in participating in family planning is the satisfaction of the acceptor with the services of health facilities. This study was conducted to find out the overview of the level of satisfaction of family planning acceptors with MKJP services. This study uses a type of quantitative descriptive research. The number of samples in this study was 56 respondents of Women of Childbearing Age (WUS), data collection was obtained using questionnaires distributed to WUS who received MKJP family planning services at the Poasia Health Center, the data obtained will be analyzed using SPSS version 24 in the form of a frequency distribution table. The study's findings included satisfaction levels in the